Association between socioeconomic background and cancer: An ecological study using cancer registry and various community socioeconomic status indicators in Kanagawa, Japan - Satoru Kanda; Kaname Watanabe; Sho Nakamura; Hiroto Narimatsu (PLoS ONE, 2025)
Information on the association between socioeconomic status (SES) and cancer is useful for policy-based cancer control. However, few studies have investigated the association between each community SES indicator and cancer. Therefore, here, we investigated the relationship between community land price, neighborhood income, education level, employment rate, and morbidity and mortality rates for lung, stomach, colorectal, liver, and breast cancers. We obtained cancer patient data from the Kanagawa Cancer Registry and SES indicator data from public databases from 2000 to 2016. We classified the data according to the year, sex, and community. Poisson regression analyses were conducted for each SES indicator, using one SES indicator as the explanatory variable and the morbidity or mortality of cancer as the response variable. The largest inverse regression coefficient for the community SES indicator was −0.91 (95% CI −1.11, −0.70) found in a model where liver-cancer mortality was the response variable and employment rate was the explanatory variable for women. Community neighborhood income and employment rate demonstrated significant inverse associations across many models. Areas with low community neighborhood income or employment rates may have more individuals at a higher risk of cancer; these SES data could help to identify locations where cancer control should be focused.